(untitled) (Scholars’ Journal, 2020)
Multiliteracies is a pedagogical approach developed in 1994 by the New London Group (NLG) that aims to make classroom teaching more inclusive by addressing cultural and linguistic diversity, and rapid development in communication channel and technology. The purpose of this study was to explore the early grade teachers’ perception on multiliteracies pedagogy and their awareness, skills and proficiency on it. We used critical ethnography research design to obtain rich and in-depth data from five years’ experienced three early grade teachers through interviews and participant classroom observation in a community school of Nepal. Interviews and class observation of teachers were audio-recorded, and recorded data were transcribed assigning codes, and main two themes were developed in terms of the codes. Regarding understanding and awareness on multiliteracies pedagogy, the findings reveal that the teachers do not have more clear theoretical concept on it. They perceive multiliteracies as being literate not only through reading and writing but also using pictures, signs, symbols and mimics. They are aware in the use of multiliteracies pedagogy to make teaching learning effective but they do not have sufficient skills and proficiency on it. They can apply multiliteracies pedagogy in early grades effectively if their knowlwdge and skills is developed through training and capacity development programme on it.